Representasi Maskulinitas dalam Iklan Extra Joss 2023 “Laki Buktikan!” Berdasarkan Perspektif Sara Mills - Arengga Melati Swandari; Anindi Nurhayati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
Male masculinity is a common theme in advertising. These potrayals often depict men as hardworking, resilient, and physically strong, thereby shaping an ideal male identity. This study uses Sara Mills’ critical discourse analysis perspective to examine the representation of the 2023 Extra Joss advertisement “Laki Buktikan!”. A qualitative descriptive approach is used, with data in the form of visuals, verbal narratives, and slogans that appear in advertising videos accessed via the TikTok application. The analysis will focus on the subjects and objects in the advertisement, the representation of masculinity, the position of the audience, the narrative structure, and the surrounding social context and gender ideology. The result of study show that the advertisement represents masculinity as an identity that must be continuously proven through strength, physical toughness, endurance, and a never-give-up attitude. Failure, defeat, and adversity are not condition that must be passively accepted, but rather condition demanding an active response from men to take concrete action. The advertisement not only promotes product, but also reproduces the ideology oh hegemonic masculinity by linking male self-proving to consuming Extra Joss energy drinks.